Maternal and neonatal factors related to prematurity - Laura Leismann de Oliveira; Annelise de Carvalho Gonçalves; Juvenal Soares Dias da Costa; Ana Lucia de Lourenzi Bonilha (SciELO, 2016)
ABSTRACT OBJECTIVE To identify maternal and neonatal factors associated with prematurity in the municipality of Porto Alegre. METHOD This was a population-based case-control study. The cases were newborns under 37 weeks of gestation and the controls were newborns over 37 weeks. The data came from the records of 19,457 births in the city of Porto Alegre in the year 2012 from the Information System on Live Births of the Municipal Health Department. The analysis was carried outand adjusted by a Logistic Regression according to a hierarchical model. The variables studied were allocated into three hierarchy levels: sociodemographic variables; reproductive history; and gestational and birth factors. RESULTS There were 767 cases allocated and 1,534 controls in a design of a case for two controls (1:2) by simple randomization. In the final model, a statistically significant association was found for prematurity for the following variables: mother's age under 19 years old (OR=1.32; CI 95%: 1.02-1.71) or over 34 years old (OR=1.39; CI 95%: 1.12-1.72); inadequate maternal schooling for age (OR=2.11; CI 95%: 1.22-3.65); multiple pregnancies (OR=1.14; CI 95%: 1.01-1.29); C-section (OR=1.15; CI 95%: 1.03-1.29); birth weights under 2,500g (OR=4.04; CI 95%: 3.64-4.49); Apgar score at five minutes between zero and three (OR=1.47; CI 95%: 1.12-1.91); and inadequate prenatal care (OR=1.18; CI 95%: 1.02-1.36). CONCLUSION The present study showed the most immediate consequence of prematurity for newborns by evidencing its association with worse Apgar scores and low birth weight. The following factors were also shown as possible more distal determinants of prematurity: mother's age; inadequate maternal education; multiple gestation; inadequate prenatal care; and C-section.